Genome-wide analyses reveal clustering in Cannabis cultivars: the ancient trilogy of a panacea - Henry, Philippe (PeerJ PrePrints, 2015)
In the present research, I used an open access data set (Medicinal Genomics) consisting of nearly 200'000 genome-wide single nucleotide polymorphisms (SNPs) typed in 28 cannabis accessions to shed light on the plant's underlying genetic structure. Genome-wide loadings were used to sequentially cull less informative markers. The process involved reducing the number of SNPs to 100K, 10K, 1K, 100 until I identified a set of 42 highly informative SNPs that I present here. The two first principal components, encompass over 3/4 of the genetic variation present in the dataset (PCA1 = 48.6%, PCA2= 26.3%). This set of diagnostic SNPs is then used to identify clusters into which cannabis accession segregate. I identified three clear and consistent clusters; reflective of the ancient trilogy of the genus Cannabis.
Keywords: Cannabis Genetics; SNP; Cannabis; sativa; indica; ruderalis